Quantification of crustacean tropomyosin in foods using high‐performance liquid chromatography–tandem mass spectrometry method. (18th March 2021) - Wang, Jianhua; Ge, Minmin; Sun, Lirui; Ahmed, Ishfaq; Li, Wenjie; Lin, Hang; Lin, Hong; Li, Zhenxing
Abstract: BACKGROUND: Allergic reactions to crustacean products have been increasing owing to the rising consumption. Tropomyosin (TM) is the main crustacean allergen; it has a coiled‐coil structure, which shows stability to various food processing methods. Crustacean processed products have been used in several food products, thereby causing greater difficulties in detecting TM in these products. We aimed to develop an assay based on high‐performance liquid chromatography–tandem mass spectrometry for the accurate and reproducible quantification of crustacean TM in foods. RESULTS: The three peptides IQLLEEDLER, LAEASQAADESER, and IVELEEELR were selected as peptide markers, and the peptide IVELEEELR was selected as the quantitative marker. Extraction conditions and enzymatic digestion conditions were completely optimized. The extraction solution of Tris–hydrochloric acid buffer (50 mmol L −1, pH 7.4) containing 1 mol L −1 potassium chloride and the enzymatic treatment at 1:15 ratio (enzyme/protein, m/m) for 13 h showed excellent efficiency. The method exhibited a good linear relationship, with the qualified coefficient of determination ( R 2  = 0.9994) in the wide range of 1 to 1000 μg L −1 . The accuracy was validated based on spiked recovery at three spiking levels (12.5, 25.0, and 50.0 μg kg −1, TM/matrix) in blank matrices that included chicken sausages, beef balls, and egg–milk biscuits. The recoveries ranged from 91% to 109% with qualified relative standard deviations <15% with the limit of quantification (of 1.6 mg kg −1, TM/matrix). CONCLUSION: This new approach can be used for the qualitative and quantitative detection of crustacean TM in various food matrices. © 2021 Society of Chemical Industry.